The history of Nyafaru Farm as a site of political struggles from the 1960s up to 2016 - Mabvudza, Shadreck Kudzai (Midlands State University, 2020)
The project intended to review the political history behind the Nyafaru Farm that led it to be the site of the political struggles in the Tangwena community from the 1960s to 2016. From the study, there are three main political factors identified that contributed to brought Nyafaru Farm as site of political struggles in Tangwena. Firstly, the land rights contradictions between the Tangwena people and the white farmer Hanmer during colonial era in 1966. The Tangwena people claimed that they have the ancestral land right on the Tangwena land, while the white farmer argued that the land was a European land, using the Land Apportionment Act of 1930 as his land right. The political struggles of evictions depending on the period started during that time up until 2016. Secondly, the formation of the Nyafaru Development Company became the backbone of the political struggles at Nyafaru Farm because it linked the farm with the political struggles. Nyafaru Development Company directors became inconsiderate on the farm during the post- independent era, which was against their main objectives from the inception of the company and against the Tangwena’s land right. Lastly, the result was the struggle for the eviction of the company and its directors from the farm and also put the farm with its activities to an end to avoid any possible oppression in future through that farm, which was achieved on 07th September 2016 after fourteen years of struggle. The qualitative methodology was applied whereby the author used interviews, focus group discussions and observations.